ALK and PD-L1 Expression in Non-Small Cell Lung Cancer through Immunohistochemical Assays in Indonesia - Syahruddin, Elisna; Sayekti, Mutia A.; Yuliyanti, Sayekti; Thabrany, Hasbullah; Nurmadani, Labbaika (Perhimpunan Dokter Paru Indonesia (PDPI)/The Indonesian Society of Respirology (ISR), 2025)
Background: Advanced therapies for non-small cell lung carcinoma (NSCLC), such as targeted therapy and immunotherapy, are available; however, their use depends on biomolecular testing. In the Indonesian context, EGFR testing is covered by the national health insurance (JKN). According to the Indonesian Clinical Guideline for Lung Cancer, if the EGFR test is negative, further testing, including ALK and PD-L1 immunohistochemistry, is required. Nevertheless, the JKN does not currently cover ALK and PD-L1 IHC tests, which restricts access to the appropriate therapies. This study aims to determine the positivity rates of ALK and PD-L1 IHC tests. Method: This study employs a cross-sectional approach to analyze 2,553 ALK and PD-L1 IHC tests conducted from 2019 to 2023, sourced from four major provinces in Indonesia Results: The positivity of ALK IHC tests is 8% with a median age of 52 years. The positivity rate for PD-L1 IHC in all patients is 49%, while based on the tumour proportion score (TPS), TPS ≥50% is 17% and TPS 1-49% is 32%. ALK positivity correlates with age and female gender (P<0.001 and P=0.006). Conversely, PD-L1 positivity was significantly associated with cancer type (P=0.008). Conclusion: ALK positivity in NSCLC in Indonesia is relatively high (8%), with a relatively young median age of 52 years and is predominantly found in females. PD-L1 positivity does not significantly differ by gender and age, but positively correlates with adenocarcinoma cancer type.